2012
DOI: 10.1021/la300634v
|View full text |Cite
|
Sign up to set email alerts
|

Diblock-Copolymer-Coated Water- and Oil-Repellent Cotton Fabrics

Abstract: A diblock copolymer consisting of a sol-gel-forming block and a fluorinated block was used to coat cotton fabrics, yielding textiles that were highly oil- and water-repellent. The coating procedure was simple. At grafted polymer amounts of as low as 1.0 wt %, water, diodomethane, hexadecane, cooking oil, and pump oil all had contact angles surpassing 150° on the coated cotton fabrics and were readily rolled. The liquids were not drawn into the interfiber space by the coated fabrics. Rather, droplets of the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 23 publications
0
76
0
Order By: Relevance
“…The product (0.84 g) was obtained as a white precipitate in an 82% yield. 1 PEG 113 -SCOCH 3 . PEG 113 -OTs (600 mg, 1.15 × 10 −4 mol) was dissolved into anhydrous DMF (in 3.0 mL) in a round-bottom flask before potassium ethanethioate (66 mg, 5 equiv) was added to this solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The product (0.84 g) was obtained as a white precipitate in an 82% yield. 1 PEG 113 -SCOCH 3 . PEG 113 -OTs (600 mg, 1.15 × 10 −4 mol) was dissolved into anhydrous DMF (in 3.0 mL) in a round-bottom flask before potassium ethanethioate (66 mg, 5 equiv) was added to this solution.…”
Section: Methodsmentioning
confidence: 99%
“…The resultant white precipitate was dried under vacuum at room temperature, yielding 510 mg of the product in an 85% yield. 1 PEG 113 -SH. PEG 113 -SCOCH 3 was converted into PEG 113 -SH using a literature method that had been employed on organic molecules.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cotton fabrics that were coated with a fluorinated azide-bearing triblock copolymer exhibited a high WCA (155°) with a copolymer concentration of only 0.25 wt%. Xiong et al reported that a fluorinated diblock copolymer bearing isopropyloxysilane groups produced superhydrophobic cotton fabrics through hydrolysis and condensation reactions between the isopropyloxysilane groups and the hydroxyl groups of the cotton substrate [140]. Meanwhile, radiation-induced graft polymerization of a fluoromonomer onto the surface of cotton fabrics provided stable coatings that retained hydrophobicity even after 50 accelerated laundering cycles, but to accomplish this the grafting degree had to exceed 10 wt% [139].…”
Section: Fluorosilicones and Fluoropolymers In Special Applicationmentioning
confidence: 99%